Issues of computer ethnics in information system and society /editor Norazmah Suhailah Abdul Malek - Meysam Namayandeh, 1981-, author; Norazmah Suhailah Abdul Malek editor; Maslin Masrom author; Zuraini Ismail author; Ramlah Hussein author (Skudai : Universiti Teknologi Malaysia, 2008)
Includes bibliographucal references and index